2003
DOI: 10.1021/la0341456
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Discotic Liquid-Crystalline Oxadiazoles as Electron-Transport Materials

Abstract: 1a. Anhydrous K 2 CO 3 (30 g) and methyl 3,4,5-trihydroxybenzoate (10 g, 5.4 mmol) was added to a deoxygenated mixture of DMF (100 mL) and of 1-bromooctane (35 g, 0.181 mol) under nitrogen. The mixture was heated at 80 ˚C for 6 h., when the reaction was judged complete by TLC analysis. The reaction mixture was cooled to room temperature, water (500 mL) was added, and the product was extracted with diethyl ether. The combined organic extracts were washed with water and dried over MgSO 4 . After filtration, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 25 publications
1
43
1
1
Order By: Relevance
“…3,4,5-Tris(ndodecan-l-yloxy)benzohydrazide (5) was prepared as described in Refs. [47,48]. 2 0 ,3 0 -Isopropylidene guanosine (3) and 2 0 ,3 0 -Isopropylidene guanosine hemisuccinate (4) were prepared as described in Refs.…”
Section: Methodsmentioning
confidence: 99%
“…3,4,5-Tris(ndodecan-l-yloxy)benzohydrazide (5) was prepared as described in Refs. [47,48]. 2 0 ,3 0 -Isopropylidene guanosine (3) and 2 0 ,3 0 -Isopropylidene guanosine hemisuccinate (4) were prepared as described in Refs.…”
Section: Methodsmentioning
confidence: 99%
“…By PR-TRMC measurements, charge carrier mobilities of 0.9 and 0.3 cm 2 V −1 s −1 , respectively, for crystalline and columnar LC phases of 22 were found. Zang et al, designed DLC 23 with benzene core and three (trialkoxyaryl)oxadiazole arms and reported TOF electron mobility of 1.0 × 10 −3 cm 2 V −1 s −1 in the columnar phase [72]. Geert's group reported metal free phthalocyanine based DLCs bearing peripheral alkylsulfonyl substituents (for example, 13b) as potential air-stable n-type semiconductors [73].…”
Section: N-type Discotic Moleculesmentioning
confidence: 99%
“…Furthermore, in recent studies of polymer light-emitting diodes, the oxadiazole moieties were demonstrated to possess a high potentiality for transport [22]. The charge drift mobility of oxadiazole derivatives doped in polycarbonate were studied, with the time-of-flight technique, in [23] and discotic oxadiazoles, with columnar mesophases, were proposed for applications in organic electronics [24]. The introduction of oxadiazole moieties to polymer main chains and to mesogens in liquid crystalline compounds is expected to tune the electroluminescence efficiency and the transport properties.…”
Section: Oxadiazoles For Electroluminescencementioning
confidence: 99%